Kedudukan Informed Consent Dalam Hubungan Dokter Dan Pasien - Irfan, Irfan (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Informed Consent can be defined as a statement of the patient or legitimately representing him in the form of an agreement on a medical action plan submitted by a doctor after receiving sufficient information to be able to make an agreement or rejection. The signing of the written informed consent form is only an affirmation of what was previously agreed. The purpose of the complete explanation is so that the patient determines his decision according to the patient's choice (informed decision). The type of research in this paper is normative legal research. The nature of this research is descriptive analytical, which is a study that describes, examines, explains and analyzes a legal regulation related to the informed consentration position in the relationship between doctors and patients. The results of this study are that before carrying out a medical action the patient has the right to obtain information on medical actions to be carried out to him as stipulated in the Minister of Health Regulation (Permenkes) No. 290 of 2008 concerning Medical Action Approval, if viewed in terms of form, the informed consent consists of Imflied consent (considered given) and expressed consent (stated), the presence of informed consent is very important in the relationship between doctors and patients where informed consent is the basis or foundation to take medical action against patients.